2006
DOI: 10.1128/jcm.00945-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genotypes of Enterocytozoon bieneusi from Stool Samples from Human Immunodeficiency Virus-Infected Patients in Thailand

Abstract: We identified genotypes of Enterocytozoon bieneusi from 33 stool samples of Thai human immunodeficiency virus (HIV)-infected adult patients. Genotype D was identified at the highest frequency (36.4%), while genotype E was the second most common (15.1%). Genotypes O and PigEBITS 7, previously found only in pigs, were observed in Thai HIV-infected patients. Phylogenetic analysis supported a zoonotic nature for E. bieneusi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
56
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 24 publications
(19 reference statements)
7
56
2
1
Order By: Relevance
“…The results of this study showed that of 160, 14 samples were positive for E. bieneusi and of the 14 samples, 12 cases were detected as genotype D. Consistent with our findings, genotype D has been reported as the most frequent genotype in most studies (24). In Thailand, Leelayoova et al, in 2006, demonstrated that genotype D with 36.4% had the highest prevalence of genotype in AIDS patients and the phylogenetic analysis suggests the zoonotic potential of the parasite (25). Our findings, besides other studies, indicate that genotype D is in most of the immunodeficient patients and animals that could be associated with the widespread potential of the genotype.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study showed that of 160, 14 samples were positive for E. bieneusi and of the 14 samples, 12 cases were detected as genotype D. Consistent with our findings, genotype D has been reported as the most frequent genotype in most studies (24). In Thailand, Leelayoova et al, in 2006, demonstrated that genotype D with 36.4% had the highest prevalence of genotype in AIDS patients and the phylogenetic analysis suggests the zoonotic potential of the parasite (25). Our findings, besides other studies, indicate that genotype D is in most of the immunodeficient patients and animals that could be associated with the widespread potential of the genotype.…”
Section: Discussionsupporting
confidence: 88%
“…Both genotypes have previously been recovered in humans but also in various animals, including pigs, muskrats, and beavers. A predominance of genotypes D and E, which are associated with a zoonotic potential, has already been described in Thailand (17). In this study, authors reported a higher frequency of genotypes D (36.4%) and E (15.2%) among HIV-infected patients.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, many genotypes have a zoonotic potential (like genotypes D, E, and K) because they are non-host specific and encountered in various mammals, including humans (21). As several studies indicate that the genotypes of E. bieneusi can differ in different geographical locations (6), it has been recently proposed that predominant genotypes in different geographical sites could be related to distinct sources of transmission (17). The comparative analysis of E. bieneusi genotypes recovered in Niamey and Hanoi produced interesting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found in numerous diverse animals (swine, cattle, macaque, muskrat, raccoon, beaver, fox, dog, and falcon) (47). The type D genotype was commonly reported to occur in HIV-positive patients in Thailand (24) and Peru (42) and in two isolated cases in Europe (36,37), and it was recently isolated from 3 HIV-negative individuals in Cameroon (3), which confirms the wide spread of this genotype. Genotype D represents 15% of isolates from four species of wildlife animals in North America (43) and 26% of isolates found in cats in Colombia (39), supporting a zoonotic route of transmission for this strain.…”
Section: Discussionmentioning
confidence: 67%